SENYAWA AKTIF ANTIMAKANDARI UMBI GADUNG (Dioscorea hispida Dennst) - Sri Rahayu Santi (Jurnal Kimia (Journal of Chemistry), 2010)
Isolation and identification of active antifeedant compounds from gadung tuber (Dioscorea hispida Dennst)has been carried out. As much as 12.03 g of concentrated methanol extract was resulted from 5.0 kg dry gadung tuberthat was macerated using methanol. Further, this extract was partitioned with n-hexane to obtain 2 concentratedextracts in n-hexane and methanol. The result of antifeedant test showed that the methanol extract was more activethan the n-hexane extract.Separations of the methanol extract using column chromatography (stationary phase : silica gel 60, mobilephase : methanol-chloroform 6:5) resulted four fractions. The most active fraction, FA , showed 2 spots on the TLC,so it was separated using preparative TLC which resulted in 2 fractions (FA.1 and FA.2). The antifeedant activity ofFA.1 fraction was higher than FA.2 fraction and it gave only 1 spot on the TLCThe result of identification using phytochemical test and spectrophotometer analysis suggested that FA.1fraction was alkaloid compound whose maximum wave length was 277.1 nm and it contained N-H (3425.3 cm-1), CHaliphatic (2927.7 and 2854.5 cm-1), C=O (1735.8 cm-1), C-N (1110.9 cm-1) and N-C=O (621.9 cm-1).